CeO2/Mn3O4 Nanocrystals: Epitaxially Strained CeO2/Mn3O4 Nanocrystals as an Enhanced Antioxidant for Radioprotection (Adv. Mater. 31/2020). Issue 31 (4th August 2020) - Han, Sang Ihn; Lee, Sang‐woo; Cho, Min Gee; Yoo, Ji Mun; Oh, Myoung Hwan; Jeong, Beomgyun; Kim, Dokyoon; Park, Ok Kyu; Kim, Junchul; Namkoong, Eun; Jo, Jinwoung; Lee, Nohyun; et al.
Abstract : Tuning the surface strain of inorganic nanozymes can enhance catalytic reactivity to scavenge reactive oxygen species (ROS). In article number 2001566, Kyungpyo Park, Taeghwan Hyeon, and co‐workers present epitaxially strained CeO2 /Mn3 O4 nanocrystals as a highly catalytic antioxidant that can protect tissue‐resident stem cells from ionizing‐radiation‐induced ROS damage.